Factor the high-degree polynomial 2x^5−4x^3+2x to solve the polynomial equation 2x^5−4x^3+2x=0.(1 point)

1 answer

To factor the polynomial \( 2x^5 - 4x^3 + 2x \), we can start by factoring out the common factor from each term.

  1. Identify the common factor, which is \( 2x \): \[ 2x^5 - 4x^3 + 2x = 2x(x^4 - 2x^2 + 1) \]

  2. Now, we need to factor the polynomial \( x^4 - 2x^2 + 1 \). We can use substitution to make this easier. Let \( y = x^2 \). Then, we can rewrite the polynomial as: \[ y^2 - 2y + 1 \]

  3. Now, factor \( y^2 - 2y + 1 \): \[ y^2 - 2y + 1 = (y - 1)^2 \]

  4. Substitute back \( y = x^2 \): \[ (x^2 - 1)^2 \]

  5. Recognizing that \( x^2 - 1 \) can be factored further: \[ x^2 - 1 = (x - 1)(x + 1) \]

  6. Thus, we have: \[ (x^2 - 1)^2 = [(x - 1)(x + 1)]^2 = (x - 1)^2(x + 1)^2 \]

Now, putting everything together, we can write: \[ 2x^5 - 4x^3 + 2x = 2x \cdot (x^2 - 1)^2 = 2x \cdot (x - 1)^2 \cdot (x + 1)^2 \]

Now we can set the equation \( 2x^5 - 4x^3 + 2x = 0 \):

\[ 2x \cdot (x - 1)^2 \cdot (x + 1)^2 = 0 \]

Thus, the solutions to the equation are:

  • From \( 2x = 0 \), we get \( x = 0 \).
  • From \( (x - 1)^2 = 0 \), we get \( x = 1 \) (with multiplicity 2).
  • From \( (x + 1)^2 = 0 \), we get \( x = -1 \) (with multiplicity 2).

Therefore, the complete factorization is: \[ 2x(x - 1)^2(x + 1)^2 = 0 \] This gives the solutions \( x = 0, 1, -1 \).